Mental Process In Bruno Mars Song Lyrics (A Systemic Functional Linguistics Perspective) - Hayati Yati (ELITE: Journal of English Language and Literature, 2016)
The data of this research taken from  the lyrics of the song by Bruno Mars from several songs entitled Treasure, Just The Way You Are, It Will Rain and Marry You as an object. The researcher uses qualitative descriptive design because the data and research question models are descriptive. This research data collected through downloading, reading, identifying, coding and classifying. The results of this research shown that in the lyrics of the song by Bruno Mars, there are aspects of the mental process namely aspects of thinking, wanting, feeling and seeing and from these findings researcher found 11 data containing the aspects of mental processes, it can be seen from this research that aspects of thinking are more dominant, namely found 5 data, aspect of wanting 3 data, aspect of seeing 2 data and aspect of feeling only found 1 data. The mental process aspect is determined based on the senser, process and phenomenon which are implicit criteria to determining the use of the mental process aspects itself.